ANALYSIS OF FACTORS INFLUENCING USER INTENTION IN USING OVO APPLICATION - Yugo Falafrima Putra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
In this era, technology development has provided many innovations in transaction. Nowadays, there is a popular trading system called mobile payment. The use of mobile payment transaction slowly changes the culture in Indonesia. This study examines the factors that influencing user interest in using OVO applications. In order to do so, this study use perspective of Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology 2 (UTAUT2). The author uses quantitative research method for this study. The data was collected using questionnaires. The respondents were 322 undergraduate students of accounting department in Universitas Brawijaya Malang, who have experience in using OVO application services. The data and hypothesis were analyzed using Structural Equation Model (SEM) based on Partial Least Square (PLS). These research findings indicate that intention to use OVO application is determined by Ease of Use, Perceived Usefulness, Perceived Risk, Price Value, and Social Influence towards Behavioral Intention to do a transaction using OVO application services. The results show that all variables are significant influence towards the behavioral intention to use OVO application services. Moreover, all of the variables have positive influence, except perceived risk variable. Keywords: Mobile Payment, Behavioral Intention, Ease of Use, Perceived Usefulness, Perceived Risk, Price Value, and Social Influence.